Overconsolidation Characteristics of Silt Layer in the Guangdong-Hong Kong-Macao Greater Bay Area - Dashu Guan; Wei Zhang; Guoqing Zhou; QiYin Zhu; Jiaqiang Zou; Jiaxi Zheng; Wenhao Huang (Advances in Civil Engineering)
In practical engineering projects, overconsolidation plays an irreplaceable role in the calculation of silt consolidation settlement. Based on a series of systematic consolidation tests conducted on reconstituted soft clay in different cities of the Guangdong-Hong Kong-Macao Greater Bay Area, the overconsolidation behavior of soft clay under different depths was studied. According to these tests, the shape of the curves of the overconsolidation ratio with depth was similar to that of the compression curves. Moreover, the deeper the silt depth is, the smaller the overconsolidation ratio is. Hence, the overconsolidation state eventually changes to the underconsolidation state. On this basis, the depths of normal consolidation were calculated through the fitting curves of the overconsolidation ratio with depth by CurveExpert1.4, which is strongly dependent on both the average thickness of the overfill and the range of water level. Based on the results, a polynomial relationship between overconsolidation ratio (OCR) and sampling depth (h) is established. This study can serve as a basis for predicting the consolidation settlement of the silt layer more accurately in practical engineering applications.